Multi-metal oxide/N-doped reduced graphene oxide modified electrode for ultrasensitive determination of phenobarbital - Seyed Saman Nemati; Gholamreza Dehghan; Simin Khataee; Zohreh Shaghaghi (Sensing and Bio-Sensing Research)
Phenobarbital (PB) is known for its sedative and anticonvulsant characteristics, making it a critical agent for the management of epilepsy and seizure disorders. Considering its narrow therapeutical range, accurate monitoring of this drug is highly recommended to prevent side effects. Herein, we successfully introduced trimetallic graphene oxide-based nanocomposite consisting of cerium oxide, nickel oxide, and copper oxide (III@N-rGO), which benefits the synergistic properties of each compound for electrochemical sensing applications. The structure of the nanostructures was evaluated using Fourier transform infrared spectroscopy (FT-IR), X-ray diffraction pattern (XRD), Raman spectroscopy, field emission scanning electron microscope images (FE-SEM), and transmission electron microscope (TEM). Various electrochemical techniques were employed to investigate the sensor's electrocatalytic performance, following the carbon paste electrode's construction. The target electrode represented superior sensing efficiency, including a broad linear range of 0.1–840 μM, proper sensitivity of 1.389 ± 0.013 mA μM−1 cm−2, low detection limit of 9.10 ± 0.002 nM at the optimum potential of 0.72 V. Furthermore, III@N-rGO electrode illustrated good long-term stability, good reproducibility, and excellent selectivity. The results of recovery tests in human serum and pharmaceutical samples (94–106 %) with desired RSD values (below 3 %) demonstrated the practical applicability of the case-studied sensor. Hence, the proposed platform has the potential to serve as a promising model for PB detection.